Cutaneous Leukocytoclastic Vasculitis in Jose R. Reyes Memorial Medical Center: A 12 year Retrospective Study - S. Bajracharya; D.K. Ismael; M.L.A. Venida (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Leukocytoclastic vasculitis (LCV) is the commonest vasculitis of skin affecting small vessels.